Practices of Transformation – Transformation of Practices: Essays in Honour of Helene Basu - Koch, Julia; Kurz, Helmar; Pande, Mrinal; Strauss, Annika (TESTINSTANZ: Wissenschaftliche Schriften der Universität Münster, 2022)
This volume is in honour of Helene Basu, whose scholarship has influenced and offered novel perspectives across fields as varied as kinship, religion and health. By integrating anthropological and historiographic approaches in her analyses of post-colonial India, she provided new lenses through which to understand the transformability of practices. Inspired by her insights, the contributors demonstrate the impact of Basu's work on their own, presenting accounts of changes in social relations and the accompanying shifts in the symbolic representations of practices and objects. Each contribution focuses on particular transformations, variously taking into account practices as diverse as drumming, wood-carving, narrating, photography, lithography and televised auctioning. By examining these and other practices, the authors attend to both translocal relationships as well as historical contexts. While new practices effect social change, practices themselves transform. Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-94059473734 ISBN978-3-487-16154-9 (Druckausgabe Georg Olms Verlag)978-3-8405-0265-1 (elektronische Version) Paperback, xx, 311 Seiten